Complexation and electronic communication between corannulene-based buckybowls and a curved truxene-TTF donor - Gallego, Maria; Calbo, Joaquin; Krick Calderon, Rafael; Pla, Paula; Hsieh, Ya-Chu; Perez, Emilio M.; Wu, Yao-Ting; Orti, Enrique; Guldi, Dirk Michael; Martin, Nazario (Chemistry - A European Journal, 2017)
The association behavior of an electron-donating, bowl-shaped, truxene-based tetrathiafulvalene (truxTTF) with two corannulene-based fullerene fragments, C32H12 and C38H14, is investigated in several solvents. Formation of 1:1 complexes is followed by absorption titrations and complemented by density functional theory (DFT) calculations. The binding constants are in the range logKa=2.9–3.5. DFT calculations reveal that the most stable arrangement is the conformation in which the 1,3-dithiole ring of truxTTF is placed inside the concave cavity of the corannulene derivative. This arrangement is confirmed experimentally by NMR measurements, and implies that a combination of π–π and CH–π interactions is the driving force for association. Timedependent DFT calculations reproduce the experimental UV/ Vis titrations and provide a detailed understanding of the spectral changes observed. Femtosecond transient absorption studies reveal the processes occurring after photoexcitation of either C32H12 or C38H14 and their supramolecular associates with truxTTF. In the case of truxTTF·C38H14, photoexcitation yields the charge-separated state truxTTFC+·C38H14·-with a lifetime of approximately 160 ps.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Association constants; Buckybowls; Donor–acceptor systems; Photoinduced charge transfer; Supramolecular chemistry